Scraps Management With Lean Six Sigma - Choong Kei Shing; Santhirasegaran Nadarajan; Sitraselvi Chandren (International Journal of Supply Chain Management, 2014)
Increasing waste and scraps reflects low productivity as ratio input to output reduces. By all means, organizations are required to kick in with ultimate objective of cost reduction through process change to improve speed, low cost raw materials, revised preventive maintenance, and manpower reduction. Asian practitioners and western practitioners develop new approach to minimize waste and be cost effective in production. In the new millennium, the established methods developed in 20th century dont seem to suffice as demand volume increases. The call for the fusion of different methods to harvest the best of different methodologies has begun. Tools and approach used are not just effective but improve robustness in production processes as well.